ANALISIS PENERIMAAN APLIKASI MCDONALD’S DENGAN MENGGUNAKAN METODE TECHNOLOGI ACCEPTANCE MODEL (TAM): Actual Use, Attitude, Behavioral Intention, McDonald’s Application, Perceived Ease of Use, Perceived Usefulness, Technology Acceptance Model - Mh. Khathamy Fhadlullah Haq Syahlevy; Pradita Eko Prasetyo Utomo; Abidin, Zainil (JURNAL AKADEMIKA, 2025)
This research aims to analyze user acceptance of the McDonald’s application using the Technology Acceptance Model (TAM) framework. TAM is a theoretical model used to understand the factors influencing technology adoption. In this study, five main variables were examined to determine the relationships between user acceptance elements: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual Use (AU). The sample size in this study consisted of 80 respondents, determined using Hair's formula. The questionnaires were distributed in two ways: by handing out paper leaflets at McDonald’s outlets and by distributing them online via Google Forms. The data analysis in this study involved testing several models and conducting hypothesis testing. The results indicate that Perceived Usefulness has a significant positive effect on Attitude Toward Using, while Perceived Ease of Use has a significant negative effect on Attitude, yet a positive influence on Perceived Usefulness. Furthermore, Attitude significantly and positively affects Behavioral Intention, and Behavioral Intention significantly influences Actual Use. These findings suggest that users’ attitudes and intentions play a crucial role in encouraging the actual use of the McDonald’s application.